EVALUATING MARKETING ACTIVITIES THROUGH THE SERVICE QUALITY IN THE FINANCIAL SECTOR - Januarko, Moehamad Unggul (Universitas Esa Unggul, 2016)
AbstractThe purpose of this first study, continuing limitations of the study AAhlak and Al-Nawas (2010) This study uses research object seven banks include Bank Mandiri, Bank Permata, BNI, BRI, Danamon, BCA, and BTN. Second to investigate and evaluate the activities of marketing and quality relationship banking arrangements. To analyze the data collected from a random sample of 124 clients drawn from the five dimensions of commercial banks in Indonesia, the quality of the relationship is used to identify the structural characteristics of the relationship between the management of the banks employees and customers. The results of the empirical research is four things. First, greater employee orientation relational and customers produce higher quality relationships. Second, a better financial providers (employees) attributes produce higher quality relationships. Third, the higher the quality of relationships that lead to better continuity of relationships. Fourth, committed client relationships generate client satisfaction, loyalty, word of mouth influence as a promotional tool. This in turn contributed to an increase in the banks image.Keywords: Quality Management and Customer Relationship Marketing Services Bakn